ChemInform Abstract: Structure and Biosynthesis of Scabichelin, a Novel Tris‐Hydroxamate Siderophore Produced by the Plant Pathogen Streptomyces scabies 87.22. Issue 45 (14th October 2013) - Kodani, Shinya; Bicz, Joanna; Song, Lijiang; Deeth, Robert J.; Ohnishi‐Kameyama, Mayumi; Yoshida, Mitsuru; Ochi, Kozo; Challis, Gregory L.
Abstract isolation and structure elucidation of scabichelin (Ia) and turgichelin (Ib)